VM placement with effective energy management in cloud using optimal VM allocation framework (OVAF) - Susmita J A Nair; T R Gopalakrishnan Nair (Institute of Advanced Engineering and Science, 2020)
The performance of servers at the data centers is affected when the servers are overloaded. To overcome this problem, the workload at the overloaded servers has to be redistributed to other servers which is possible with live VM migration. Live migration plays a crucial role in handling the overload at the data centers without service interruption. However, live migration also incurs some performance loss and energy overhead. The energy consumption at the data centers is a matter of utmost concern both in terms of economy and ecology. In this paper we are proposing a novel approach to find the most suitable server for VM placement. We have introduced an Optimal VM Allocation Framework (OVAF) in which the hosts at the source requests the destination for their available slots. Based on the response from the available servers, the utilization factor is calculated and the selection of appropriate destination for VM placement is done. Simulations carried out have shown 10% improvement in energy saving.